Shewanella sp. O23S as a Driving Agent of a System Utilizing Dissimilatory Arsenate-Reducing Bacteria Responsible for Self-Cleaning of Water Contaminated with Arsenic - Drewniak, Lukasz (Int J Mol Sci, 2015)
The purpose of this study was a detailed characterization of Shewanella sp. O23S, a strain involved in arsenic transformation in ancient gold mine waters contaminated with arsenic and other heavy metals. Physiological analysis of Shewanella sp. O23S showed that it is a facultative anaerobe, capable of growth using arsenate, thiosulfate, nitrate, iron or manganite as a terminal electron acceptor, and lactate or citrate as an electron donor. The strain can grow under anaerobic conditions and utilize arsenate in the respiratory process in a broad range of temperatures (10–37 °C), pH (4–8), salinity (0%–2%), and the presence of heavy metals (Cd, Co, Cr, Cu, Mn, Mo, Se, V and Zn). Under reductive conditions this strain can simultaneously use arsenate and thiosulfate as electron acceptors and produce yellow arsenic (III) sulfide (As(2)S(3)) precipitate. Simulation of As-removal from water containing arsenate (2.5 mM) and thiosulfate (5 mM) showed 82.5% efficiency after 21 days of incubation at room temperature. Based on the obtained results, we have proposed a model of a microbially mediated system for self-cleaning of mine waters contaminated with arsenic, in which Shewanella sp. O23S is the main driving agent.